Clinico-pathological observation of Gaucher disease type I - Naumova , O.V.; Potapov , S.M. (Морфологія / Morphologia / Morfologìâ, 2024)
Background. Gaucher disease is one of the most common autosomal recessive lysosomal storage diseases which characterize by accumulation of glucosylceramide in the macrophages what is leading to the formation of Gaucher cells in the bone marrow, liver, spleen, brain and other organs with the occurrence of clinical manifestations of varying severity and age of onset. Objective. To describe local and systemic changes in the organs at Gaucher disease type I for optimization of intravital and postmortem diagnostics. Material and methods. A description of autopsy case of Gaucher disease type I. Macroscopic and histological examination were performed using standard processing. Results. In a 24-year-old woman with clinically diagnosed in childhood Gaucher disease type I, who died from liver and kidney failure, pathological examination revealed the formation of characteristic Gaucher cells in the liver with hepatomegaly, fibrosis and reorganization of the liver tissue, in mesenteric lymph nodes, bones, pia mater. The disease was complicated by bilateral hydrothorax, ascites, edema-swelling of the brain tissue, small multiple acute erosions of the stomach and duodenum mucosa with minor acute gastric bleeding, anemia and thrombocytopenia. Conclusion. In the presented observation, in spite of the early diagnostics of Gaucher disease, the patient did not receive appropriate therapy, what led to the development of severe complications and death at young age.